Entdeckungen in kleinen Schritten. Ergebnisse archäologischer Forschungen in Stift und Stiftskirche von Milevsko/Mühlhausen in Böhmen. - Brichácek, Pavel (Geraser Hefte, 2006)
Keywords: milevsko

Jarloch a tzv. Ansbert, aneb, Nesmělá návštěva v tvůrčí dílně prvního milevského opata - Smékalová, Anna (Sborník prací Filozofické fakulty brněnské univerzity. C, Řada historická, 2006)
The theme of this partial study about the first abbot from Milevsko is only one element from the whole comlex of the problems pertinent to the historical conception of Gerlach, namely so called Ansbert alias the History about the crusade of the emperor Friedrich I. The editors of 19"1 century destroyed this conception of Gerlach because they ripped the complex of the texts included in the contemporary Strahov manuscript. We find the only version of the chronicle of Vincenc and Gerlach in this manuscript as well as the only complete text of the chronicle of so called Ansbert. Just this set represents the conception whole, parts of which cannot stand one without the others. The existence of the chronicle of so called Ansbert in the Strahov manuscript demonstrates Gerlach's larger scope than would be expected from the old editions. The likeliness of the fact that the manuscript was written in Milevsko is confirmed by the corrections in the text made by Gerlach himself. We have to suppose not only the existence of relatively furnish monastic scriptorium in Milevsko but also the contact of the Premonstratensian monastery in Milevsko with Cistercians in monastery Heiligenkreuz, from where the pattern for the copy of the History about the crusade of the emperor Friedrich I. in Strahov manuscript came. From this follows also the phase of preparation for writer activity of Gerlach, that means acquiring the patterns, copying them, finding out another annal sources and finally building up the conception and compiling the concept, according to what writers were able to copy. If we contemplate the historical activity of Gerlach as an insert of the History about the crusade of the emperor Friedrich I., or better, of his own work between the chronicle of Vincencius and the History and in the History, the conception of Gerlach comes into a magnificent light. We see not only an author who is trying to put all his sources together but also a creator of one great complex of texts that accords with the conception of writer activity of a medieval intellectual.
Keywords: milevsko